Postnatal serum concentrations of endogenous free fatty acids in newborns admitted to the neonatal intensive care unit: effects on unbound bilirubin. (November 2014) - Koda, Tsubasa; Morioka, Ichiro; Yokota, Tomoyuki; Kurokawa, Daisuke; Fujita, Kaori; Nagasaka, Miwako; Matsuo, Kiyomi; Shibata, Akio; Sato, Itsuko; Kawano, Seiji; Yamada, Hideto; Nakamura, Hajime; et al.
Background: Few studies have reported the characterization of postnatal serum concentrations of endogenous free fatty acids (FFAs) in high-risk newborns and their effects on unbound bilirubin (UB). Methods: Serum concentrations of FFA, albumin (Alb), UB and total bilirubin (TB) were measured in 713 samples obtained within 5 days after birth from 439 newborns without intravenous lipid supplementation admitted to the neonatal intensive care unit (NICU). Serum FFA was reported as the day-specific percentile-based curve. Serum FFA and FFA/Alb ratios were compared in term and preterm patients. To assess the impact of FFA on UB, daily changes in FFA/Alb and UB/TB ratios were compared in term patients without receiving phototherapy or any drugs, and linear regression analysis was performed between FFA/Alb ratio and serum UB concentration or UB/TB ratio using 140 sera with hyperbilirubinemia of term and preterm patients. Results: A percentile-based curve showed that serum FFA peaked at 1 day of age and progressively decreased. Serum FFA and the FFA/Alb ratio were significantly higher in term than in preterm patients at birth and 1 and 3 days of age. FFA/Alb ratio significantly changed over 5 days after birth, but UB/TB ratio remained constant. FFA/Alb ratio did not correlate with serum UB concentration or UB/TB ratio in sera with hyperbilirubinemia. Conclusions: We assessed postnatal concentrations of serum FFA in a large number of high-risk newborns admitted to the NICU. The concentration of endogenous FFAs in newborns admitted to the NICU was not rising until it influenced UB.